One City, Two Systems: Democracy in an Electronic Chat Room in Hong Kong - Fung, Anthony (Javnost-The Public, 2002)
China resumed the sovereignty of Hong Kong from Britain in 1997. To preserve this former colony as an international finance centre, China is abided to rule Hong Kong under the philosophy of “One Country Two Systems” principle, which guarantees that the capitalism of Hong Kong remains intact within its territorial boundary, across which China’s communism is the dominant ideology. However, local citizens started to question the authorities’ determination to preserve the principle soon after 1997, when self-censorship in traditional media was notorious and they conceived that the continuity of press freedom and other democratic practice were being eroded. Under this critical period of public anxiety, the proliferation of online media gives the residents a ray of hope. The public seems to believe that these new communication media create a free and autonomous space and an emerging online community relatively immune to official controls. Such protection comes from the public’s unconscious construction of a “one city, two systems” ideal – an analogy of the “One Country Two systems.” This paper aims, through a case study of an electronic chat room of an online newspaper, to examine whether it is possible for local citizens to engage in a democratic form of online communication. In the wake of a closed political environment, the search for minimally free political practices in these spaces has serious implications for the dominated public to engage in democratic struggle. The significance of this study lies in theorising about such a form of democracy and, practically, it sheds light on the potentiality and possibility of political struggle in a region under political domination by an authoritarian state. The paper concludes that forms of organised domination exist in the chat room. The chat room becomes a polarised site of struggle where authorities and citizens engage, disparage and overwhelm each other.